Euro – How Big a Difference: Finland and Sweden in Search of Macro Stability - Paavo Suni; Vesa Vihriälä (The Research Institute of the Finnish Economy (ETLA), 2013)
The euro crisis has rekindled questions about the advantages and disadvantages of membership in the European Monetary Union. In the Northern periphery of the EU, the different monetary regime choices of Finland and Sweden have created a particularly interesting testing ground for the benefits of the EMU. The average growth rates were rather similar before the Great Recession that started in the autumn of 2009, while Sweden has grown faster since that. In terms of price stability Sweden has fared somewhat better than Finland in the EMU period. We assess the effects of the regime choice by simulating the behaviour of the Swedish economy with National Institute's Global Econometric Model (NiGEM) on the assumption that Sweden had joined the EMU in 1999. The simulation exercise suggests that the independent monetary regime reduced the impact of the global shock on Sweden. The different monetary regimes cannot, however, explain the growth gap between Sweden and Finland anymore in 2012. Other factors, such as the decline of the Nokia cluster, are needed for that. As a whole, our results suggest that the different choices with regard to the EMU have not affected the macroeconomic outcomes very much.
Keywords: C15; F17; F37; P52; 330; Finland; Sweden; EMU; Simulation; Counter factual; Währungssystem; Eurozone; Wirkungsanalyse; Simulation; Finnland; Schweden